Gaze transitions when learning with multimedia - Krzysztof Krejtz; Andrew T. Duchowski; Izabela Krejtz; Agata Kopacz; Piotr Chrząstowski-Wachtel (Bern Open Publishing, 2016)
Eye tracking methodology is used to examine the influence of interactive multimedia on the allocation of visual attention and its dynamics during learning. We hypothesized that an interactive simulation promotes more organized switching of attention between different elements of multimedia learning material, e.g., textual description and pictorial visualization. Participants studied a description of an algorithm accompanied either by an interactive simulation, self-paced animation, or static illustration. Using a novel framework for entropy-based comparison of gaze transition matrices, results showed that the interactive simulation elicited more careful visual investigation of the learning material as well as reading of the problem description through to its completion.